2008
DOI: 10.1080/08880010802234911
|View full text |Cite
|
Sign up to set email alerts
|

SENSORY NEURAL HEARING LOSS IN Β-Thalassemia MAJOR PATIENTS TREATED WITH DEFEROXAMINE

Abstract: This study evaluated the incidence of sensory neural hearing loss (SNHL) in beta-thalassemia major patients treated with deferoxamine in Mofid Children's Hospital. Based on the patients' file review, this descriptive and cross-sectional study was performed in all thalassemia patients older than 5 years old who were treated with regular blood transfusion and deferoxamine pump injection during the year 2006. The first visit with the otolaryngologist was performed in all patients to demarcate the presence of ceru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 6 publications
1
15
3
Order By: Relevance
“…Ototoxicity was seen at an older age in our study and, consistent with previous studies, there was no relationship of ferritin or pre-tx Hb level between the ototoxicity and non-ototoxicity groups (p=0.705) [1,4,6] . Ototoxicity was, however, significantly associated with duration of DFO use (Pearson Chi-Square test, p<0.05).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Ototoxicity was seen at an older age in our study and, consistent with previous studies, there was no relationship of ferritin or pre-tx Hb level between the ototoxicity and non-ototoxicity groups (p=0.705) [1,4,6] . Ototoxicity was, however, significantly associated with duration of DFO use (Pearson Chi-Square test, p<0.05).…”
Section: Discussionsupporting
confidence: 80%
“…Ambrosetti et al [12] reported that there was no correlation between ototoxicity and age or ferritin level. Similarly, Shamsian et al [1] reported no relationship between ferritin level, duration of DFO therapy, or dosage (48.9±9.6 mg/kg/day) of DFO therapy with hearing loss; also, Styles and Vichinsky [14] found no significant difference between ototoxicity and non-ototoxicity groups with respect to age, DFO dose, length of chelation, or ferritin level. In contrast, Porter et al [9] concluded that DFO ototoxicity was related to high dosage and low ferritin levels, and in a large series (283 cases) analyzed by Faramarzi et al [4] the incidence of ototoxicity, occurring only in those taking doses greater than 50 mg/kg/day, was 3.5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Regular blood transfusions are carried out in patients with BTM starting from childhood to improve quality of life, and increase survival. 2 Regular blood transfusions result in iron deposition, in other words secondary chromatosis, which causes various organ dysfunctions, such as hepatic fibrosis and cirrhosis, hyperpigmentation of skin, diabetes mellitus, hypogonadism, pulmonary dysfunction, and cardiac disorders. 3 Iron-chelating agents are used to decrease complications related to transfusion-induced hemochromatosis in patients BTM.…”
Section: Introductionmentioning
confidence: 99%